PENGARUH IKLAN NIVEA #EXTRACARE TERHADAP KEPERCAYAAN DIRI PEREMPUAN DI KOTA PEKANBARU - Almira Shalsabila; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Advertisements on various social media which are now also one of the most effective and efficient commercial platforms. According to the Selective Influence Theory, the same advertising persuasion will go through a process of selectivity in each audience, which in turn will shape product purchasing decisions and attitudes. In distributing advertisements and marketing products, it takes a message, concept or media that effectively influences others to be interested in the products we market or remember advertisements that are marketed well. In this case, the ad from Nivea #ExtraCare comes with a different advertising concept andp message. This study aims to determine the effect of #ExtraCare nivea advertisements on women's self-confidence.The method used in this research is quantitative research methods, and the type of research approach used is a survey. The sampling technique used is random sampling of 100 respondents obtained through the Slovin formula. The data analysis method used is simple linear regression, t test, and testing the coefficient of determination.The results of this study are: there is an effect of advertising on self-confidence in women in the city of Pekanbaru, seen from the results of the t-test analysis, it is proven that tcount (advertising) is 9.337,> t table 1.983, then Ha is accepted and Ho is rejected. The magnitude of the influence of advertising on self-confidence is 37%, this can be seen from the test results of the determinant coefficient, rcount is known to be 0.610, then to find out how much influence variable X has on Variable Y by using the determinant coefficient r2. From the calculation results obtained 37.2% rounded up to 37%. With a fairly strong category and the remaining 63% is influenced by other factors. Keywords: Advertising, Nivea and Self Confidence.